Dribble Deficit: A novel method to measure dribbling speed independent of sprinting speed in basketball players - Scanlan, A. T.; Wen, N.; Spiteri, T.; Milanovic, Z.; Conte, D.; Guy, J. H.; Delextrat, A.; Dalbo, V. J. (Journal of Sports Sciences, 2018)
Basketball tests assessing dribbling speed predicated on total performance times are influenced by sprinting speed. This study examines an approach termed Dribble Deficit to counter this limitation by examining the relationships between sprinting and dribbling speed during linear and change-of-direction (COD) tasks measured using total performance time and Dribble Deficit. Ten semi-professional basketball players completed linear sprints and COD sprints with and without dribbling. Dribble Deficit was calculated as the difference between the best time for each dribbling trial and corresponding non-dribbling trial for linear and COD sprints. Large to very large significant relationships (P < 0.05) were evident between linear sprint and dribble times (R = 0.64-0.77, R2 = 0.41-0.59), and between COD sprint and dribble times (R = 0.88, R2 = 0.77). Conversely, trivial-small relationships were evident between linear sprint time and linear Dribble Deficit (R = 0.01-0.15, R2 = 0.00-0.02). A non-significant, moderate, negative relationship was observed between COD sprint time and COD Dribble Deficit (R = -0.45, R2 = 0.20). These findings indicate Dribble Deficit provides a more isolated measure of dribbling speed than tests using total performance times. Basketball practitioners may use Dribble Deficit to measure dribbling speed independent of sprint speed in test batteries.